In vivo kinematic comparison of medial pivot total knee arthroplasty in weight-bearing and non-weight-bearing deep knee bending. (October 2022) - Kage, Tomofumi; Inui, Hiroshi; Tomita, Tetsuya; Yamazaki, Takaharu; Taketomi, Shuji; Yamagami, Ryota; Kono, Kenichi; Kawaguchi, Kohei; Murakami, Ryo; Arakawa, Takahiro; Tanaka, Sakae
Abstract: Background: This study aimed to determine the kinematics of medial pivot total knee arthroplasty by comparing weight-bearing and non-weight-bearing deep knee bending and to evaluate the effect of the weight-bearing state on the kinematics. Methods: The kinematics of 19 knees were investigated under fluoroscopy during squatting (weight-bearing) and active-assisted knee bending (non-weight-bearing) using two- to three-dimensional registration technique. Accordingly, range of motion, anteroposterior translation for the medial and lateral low contact points, axial rotation of the femoral component relative to the tibial component and kinematic pathway were evaluated. Findings: There was no difference in range of motion between the two states. The medial anteroposterior translation showed no significant movement with no anterior translation in both the weight-bearing and non-weight-bearing from 0° to 90° of flexion. Regarding the lateral anteroposterior translation, a posterior translation was observed during weight-bearing, whereas a slight anterior translation from 0° to 30° of flexion and subsequent posterior translation were found in the non-weight-bearing. Femoral external rotation was observed in the weight-bearing, whereas femoral internal rotation was seen from 0° to 30° of flexion and subsequent femoral external rotation was observed in the non-weight-bearing. The kinematic pathway showed medial pivot motion and subsequent bicondylar rollback in the weight-bearing, whereas only medial pivot motion was observed in the non-weight-bearing. Interpretation: The medial anteroposterior translation of the femur during deep knee bending showed no anterior motion in the two states. The lateral anteroposterior translation and femoral rotation were different in the mid-flexion range between the two states. Highlights: Weight-bearing and non-weight-bearing deep knee bending were evaluated. The medial side of the femur showed no anterior motion in the two states. Anteroposterior position of the lateral side differed in the mid-flexion range. Femoral rotational kinematics were different between the two states. Effect of weight-bearing on kinematics was small in the medial compartment.